Fatores associados à cessação do tabagismo sem ajuda - Pereira, Egle Sousa (2017)
Smoking is a pandemic, responsible for high rates of morbidity and mortality. Studies show that unassisted stop is the most common form of cessation, reaching 85%. However, it is not yet clear which factors are associated with this type of cessation. Objective: To analyze the factors associated with cessation of smoking without help. Methods: Cross-sectional study, involving patients aged 18 years or older, who are part of the request of the Medical Clinic Ambulatories of the Júlio Müller University Hospital (HUJM), in the city of Cuiabá, Mato Grosso (MT), Brazil, in the May to September 2016. Patients were interviewed and answered a semi-structured questionnaire covering socio-demographic, lifestyle, economic classification according to the Brazilian Association of Research Companies - ABEP (2015), stress evaluation through the Perceived Stress Scale (PSS), evaluation of the degree of nicotine dependence using the Fagerström Test, alcoholism screening test using the CAGE questionnaire and the reasons that led them to stop smoking. The data were double typed through the Epi Info 7 Program and data analysis was performed with the help of SPSS, version 23. The research project was approved by the Ethics Committee of the HUJM/UFMT. Results: A total of 808 patients, the majority of whom were female (64.4%), had a mean age of 50.7 years, married (56,9%) and had a self-reported brown color (62.5%) were evaluated. Among the 262 ex-smokers, 236 (90.1%) of them quit smoking without help and this form of cessation is associated with males (p-value = 0.04), lower level of education (p-value = 0.04), Higher smoking time (p-value = 0.03) and younger when quit smoking (p-value = 0.01). Conclusions: It was concluded that the factors associated with unassisted cessation were male, lower educational level, lower age when smoking stopped and lower smoking time. In addition, it is emphasized that the main reasons that led the patient to stop smoking without help were self-initiative, family influence and religion.